Analisis Strategi Dengan Menggunakan Porter's Five Forces Model Pada Perusahaan Kentucky Fried Chicken (KFC) Di Indonesia - Ahrina laila; Adila Misbahussururi; Titin Hartini (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to analyze KFC's business strategy using Porter's Five Forces Model. This analysis includes five competitive forces: threat of new entrants, bargaining power of suppliers, bargaining power of buyers, threat of substitute products, and competition between existing firms. Aims to understand external factors that influence a company's competitiveness in the industry. The methodology used in this research is a case study with a qualitative analysis approach. The data used was obtained through related literature, company annual reports, and other secondary sources that discuss KFC's competitive position. The analysis results show that KFC has a competitive advantage through brand strength, global distribution and product innovation, even though it faces threats from intense competition and changing trends in consumer preferences.